10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Background Plasma proinsulin concentrations are used to investigate hypoglycemia. They have also been proposed as a marker of β-cell function, particularly as a ratio with C-peptide. Immunoassays remain the primary method for measuring proinsulin despite potential limitations. Mass spectrometry-based assays have been described, but are semiquantitative or rely on nano-flow liquid chromatography. We aimed to develop a liquid chromatography-tandem mass spectrometry assay (LC-MS/MS) at typical clinical laboratory flow rates to quantify proinsulin and its partially processed forms in human plasma and ensure accuracy over time with distributable well-characterized calibrators. Methods Sample preparation consists of protein precipitation, Glu-C digestion, peptide immunoaffinity enrichment, and LC-MS/MS analysis of 2 surrogate peptides: RGFFYTPKTRREAE spans the cleavage site for des-31,32-proinsulin and GSLQKRGIVE spans the site for des-64,65-proinsulin. A purified protein calibration material was characterized (HPLC and amino acid analysis) and used to value-assign a matrix-matched single-point calibration material. Results Within-batch and between-batch imprecision were ≤12.2% and ≤16.4%, respectively. The assay was linear from 0.14 to 53.5 pM and 1.1 to 91.6 pM, with a lower limit of the measuring interval of 2.8 and 8.8 pM for RGFFYTPKTRREAE and GSLQKRGIVE, respectively. The concentration of des-31,32-proinsulin increased more during childhood than intact proinsulin. Participants with type 1 diabetes-associated autoantibodies had higher proinsulin-to-C-peptide ratios. Method comparison with 2 commercial immunoassays revealed variable cross-reactivity with insulin. Conclusion The validated assay is robust and will be a useful tool for advancing studies of β-cell function. A detailed standard operating procedure, well-characterized calibration material, and monoclonal antibodies are available for adoption in other laboratories.